Evolution in Caffeoylquinic Acid Content and Histolocalization During Coffea canephora Leaf Development - MONDOLOT, LAURENCE (Oxford University Press, 2006)
• Background and Aims Caffeoylquinic acids are cinnamate conjugates derived from the phenylpropanoid pathway. They are generally involved in plant responses to biotic and abiotic stress and one of them, chlorogenic acid (5-O-caffeoylquinic acid, 5-CQA), is an intermediate in the lignin biosynthesis pathway. Caffeoylquinic acids, and particularly 5-CQA, are accumulated in coffee beans, where they can form vacuolar complexes with caffeine. Coffea canephora beans are known to have high caffeoylquinic acid content, but little is known about the content and diversity of these compounds in other plant parts. To gain new insights into the caffeoylquinic acid metabolism of C. canephora, caffeoylquinic acid content and in situ localization were assessed in leaves at different growth stages. • Methods HPLC analyses of caffeoylquinic acid content of leaves was conducted in conjunction with detailed histochemical and microspectrofluorometrical analysis. • Key Results and Conclusions HPLC analyses revealed that caffeoylquinic acid content was 10-fold lower in adult than in juvenile leaves. The most abundant cinnamate conjugate was 5-CQA, but dicaffeoylquinic acids (particularly in juvenile leaves) and feruloylquinic acids were also present. Using specific reagents, histochemical and microspectrofluorometrical analysis showed that caffeoylquinic acids (mono- and di-esters) were closely associated with chloroplasts in very young leaves. During leaf ageing, they were found to first accumulate intensively in specific chlorenchymatous bundle sheath cells and then in phloem sclerenchyma cells. The association with chloroplasts suggests that caffeoylquinic acids have a protective role against light damage. In older tissues, their presence in the leaf vascular system indicates that they are transported via phloem and confirms their involvement in lignification processes. In accordance with the hypothesis of a complex formation with caffeine, similar tissue distribution was observed for alkaloids and this is further discussed.